2012
DOI: 10.1111/j.1524-4725.2012.02362.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma In Situ Treated Successfully Using Imiquimod After Nonclearance with Surgery: Review of the Literature

Abstract: Imiquimod appears to be beneficial in the treatment of MIS and melanoma metastases when surgical options are not feasible. Imiquimod should not be used for removal of dysplastic or atypical nevi. The treatment regimens varied from study to study, and there are no randomized controlled trials in the literature. More studies are needed to develop a reliable and reproducible treatment regimen, to fully elucidate the role of imiquimod in the treatment of MIS and melanoma, and to determine the prognostic predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 96 publications
1
49
0
2
Order By: Relevance
“…11 However, imiquimod remains an off-label indication for melanoma because of the lack of randomized, prospective trials demonstrating its efficacy compared with conventional surgery. 7,13,[17][18][19][20] A thorough discussion of risks and benefits is necessary so that patients/families understand the limitations of treatment with imiquimod over standard surgical resection, including the risk of missing or undertreating invasive melanoma, local recurrence caused by lack of histologic margin control, and absence of long-term randomized controlled trials or comparative studies. 11 Close follow-up is recommended in patients treated with imiquimod, along with a low threshold to perform ''scouting'' biopsies after treatment and biopsy of any recurrent pigmentation in imiquimod-treated sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, imiquimod remains an off-label indication for melanoma because of the lack of randomized, prospective trials demonstrating its efficacy compared with conventional surgery. 7,13,[17][18][19][20] A thorough discussion of risks and benefits is necessary so that patients/families understand the limitations of treatment with imiquimod over standard surgical resection, including the risk of missing or undertreating invasive melanoma, local recurrence caused by lack of histologic margin control, and absence of long-term randomized controlled trials or comparative studies. 11 Close follow-up is recommended in patients treated with imiquimod, along with a low threshold to perform ''scouting'' biopsies after treatment and biopsy of any recurrent pigmentation in imiquimod-treated sites.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of 46 reports on the use of imiquimod for MIS or LM, 220 of 264 (82%) patients demonstrated clinical or histologic clearance. 20 The degree of inflammation with imiquimod has been correlated with long-term clearance but depends on the clinical setting in which the agent is used. If a large clinical residual LM is evident after diagnostic biopsy, the likelihood of significant inflammatory response is high, compared with its use in the adjuvant setting, in which histologic transection of LM after attempted excision, or what may only be actinic melanocytic hyperplasia, results in little to no inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, topical imiquimod has been shown to be a good therapeutic alternative to surgical excision in patients with comorbidities or at risk of cosmetic disfigurement [20]. Imiquimod works as a topical immune response modifier, which operates through binding TLR-7/8 in neutrophils, macrophages and dendritic cells and regulates different genes involved in the immune response, oncogenesis and apoptosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…55 Imiquimod is an immune response modifier that works by activating Toll-like receptor 7 (TLR-7) and causes a localized immune response at the targeted site(s). It is approved by the US Food and Drug Administration for the treatment of superficial basal cell carcinoma, actinic keratosis, and genital warts.…”
Section: Staged Excision Key Pointsmentioning
confidence: 99%